2017
DOI: 10.1021/acs.biochem.6b01215
|View full text |Cite
|
Sign up to set email alerts
|

Noncoupled Fluorescent Assay for Direct Real-Time Monitoring of Nicotinamide N-Methyltransferase Activity

Abstract: Nicotinamide N-methyltransferase (NNMT) is an important biotransforming enzyme that catalyzes the transfer of a labile methyl group from the ubiquitous cofactor S-5'-adenosyl-l-methionine (SAM) to endogenous and exogenous small molecules to form methylated end products. NNMT has been implicated in a number of chronic disease conditions, including metabolic disorders, cardiovascular disease, cancer, osteoarthritis, kidney disease, and Parkinson's disease. We have developed a novel noncoupled fluorescence-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 52 publications
2
25
1
Order By: Relevance
“…Tables 1 and 2 summarize passive membrane diffusion and active transport membrane permeability, respectively, for select small molecule NNMT inhibitors for which structure activity relationships had been previously developed. [17] 1-MNA, a product inhibitor of NNMT[12, 24, 25] exhibited no passive permeability (Table 1). Similarly, the quinolinium containing parent analogue 1-MQ also lacked passive diffusion properties (Table 1), suggesting that the lipophilicity and drug-like permeability properties of analogues within the methylquinolinium series had to be improved via chemical modification.…”
Section: Resultsmentioning
confidence: 99%
“…Tables 1 and 2 summarize passive membrane diffusion and active transport membrane permeability, respectively, for select small molecule NNMT inhibitors for which structure activity relationships had been previously developed. [17] 1-MNA, a product inhibitor of NNMT[12, 24, 25] exhibited no passive permeability (Table 1). Similarly, the quinolinium containing parent analogue 1-MQ also lacked passive diffusion properties (Table 1), suggesting that the lipophilicity and drug-like permeability properties of analogues within the methylquinolinium series had to be improved via chemical modification.…”
Section: Resultsmentioning
confidence: 99%
“…The abnormal expression of NNMT has been widely identified in several types of tumor (22,23). It has been demonstrated that NNMT is involved in the malignant migration of tumor cells and that it may be used as a potential biomarker for predicting tumor invasion (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…After pre‐incubation at 37°C for 5 minutes, the system was primed to respond by adding SAM and detected by following the change of fluorescence intensity with emission at 405 nm and excitation at 330 nm with the interval of 2 minutes in 30 minutes using Microplate Reader. [ 19 ] The concentration of product N ‐methyl quinoline (MeQ) was determined via the MeQ standard curve. The data were processed using Michaelis‐Mentennon‐linear regression analysis.…”
Section: Methodsmentioning
confidence: 99%